Isobaric Tags for Relative and Absolute Quantitation-Based Proteomics Analysis Provides a New Perspective Into Unsynchronized Growth in Kuruma Shrimp (Marsupenaeus japonicus) - Zhao, Jichen; Liao, Minze; Lin, Zexu; Huang, Yiyi; Zhong, Yunqi; Liu, Luyao; Chen, Guoliang; Ni, Zuotao; Sun, Chengbo (Frontiers in Marine Science, 2021)
Unsynchronized growth is a common phenomenon in farmed crustaceans. The underlying molecular mechanism of unsynchronized growth of crustaceans is unclear. In this study, a comparative proteomic analysis focusing on growth differences were performed using kuruma shrimp Marsupenaeus japonicus, an economic crustacean species, as the model. The study analyzed kuruma shrimp at fast growth stage and steady growth stage from both fast growth group and slow growth group by an Isobaric tags for relative and absolute quantitation (iTRAQ)-based quantitative proteomic analysis method. A total of 1,720 proteins, including 12,291 peptides, were identified. Fifty-two and 70 differentially expressed proteins (DEPs) were identified in the fast growth stage and steady growth stage, respectively. Interestingly, 10 DEPs, including 14-3-3-epsilon-like, GPI, GPD1, MHC-1a, and MHC-1b, were presented in both growth stages. In addition, all these 10 DEPs shared the same expression tendency at these two growth stages. The results indicated that these 10 DEPs are potential growth biomarkers of M. japonicus. Proteins associated with faster growth of M. japonicus may promote cell growth and inhibit cell apoptosis through the Hippo signaling pathway. The fast growth group of M. japonicus may also achieve growth superiority by activating multiple related metabolic pathways, including glycolysis, glycerophospholipid metabolism and Citrate cycle. The present study provides a new perspective to explore molecular mechanism of unsynchronized growth in crustacean species.